Analysis Of Lesson Planning in Developing Teaching Modules in Primary Schools - Enjang Yusup Ali; Dalia Susilawati (Journal of Primary Education, 2024)
This research is motivated by learning planning using teaching modules carried out by teachers in implementing the independent curriculum in elementary schools. The purpose of this study is to explain the planning that has been implemented by elementary school teachers in Sumedang Regency. This research uses qualitative research with data collection techniques using questionnaires given to grade 1,2 and grade 4,5 teachers. The data analysis technique uses the Miles and Huberman model which consists of three stages, namely data reduction, data display and conclusion drawing. The results showed that teachers have planned lessons using teaching modules that are tailored to the components but there are some teachers who experience difficulties when preparing teaching modules. Thus, additional support and training is needed for teachers to improve their skills and provide a better learning experience for students.